Renk bilgisi ve ofset baskıda farklı renk tonlarının oluşması - Yeşiltaş, Bayram (My University, 2002)
Renk ışığın cisimlere çarparak yansımasıyla gözümüzde oluşan olguya renk denir. Işık olmadan renk olmaz yani görünmez. Renkler; genel olarak iki grup altında toplanır. Bunlar, maddesel ve ışıksal renklerdir. Maddesel renkler cyan, magenta, yellow renklerin karıştırılmasıyla siyaha yakın bir renk oluşur. Işıksal renklerde rengin kaynağı ışıktan gelen kırmızı, yeşil, mor ışığın birleşiminden beyaz ışık rengi oluşur. Bu iki farklı renk kaynağından maddesel renk karışımı ofset baskıda kullanıldığından maddesel renk karışımları incelenmiştir. Bilgisayar teknolojisi her alanda olduğu gibi matbaacılık alanında da hızla ilerlemektedir. Bu teknoloji orta ölçekli ve küçük ölçekli matbaalara kadar yayılmıştır. Bilgisayarda renk ayırımı ve düzeltme işlemleri renk geçişleri ve renge bilgisayar ekranında müdahale etmenin kuralları incelenmiştir. Ofset baskı tekniğinde; baskı yapılacak malzemenin (kağıt, karton, teneke), makinenin yeniliği, nemlendirme düzeni (alkollü, konvansiyonel), kullanılan malzemenin (film, kalıp, mürekkep, kauçuk, nemlendirme suyu ve yardımcı maddeler) kalitesi gibi faktörler baskı sonucunun kalite derecesini belirler. Kaliteli bir baskıda insan gözünde olumlu bir etki oluşturup albeni sağlar. Bunu elde edebilmek için ise rengi olumsuz etkileyen faktörlerin ortadan kaldırılması gerekmektedir. Renk ayrımı yapılacak orijinalin (basılması istenen orjinalin) baskı materyaline göre baskı makinasının seçimi ve rengin oluşmasına etkisi araştırılıp sunulmuştur. Basılı kağıdın sürtünmesi sonucunda renk bozulması test edilerek tablo halinde sunulmuştur. Rengin ışığa karşı dayanıklılığı test edilip tablo halinde sunulmuştur. Mayıs - 2002 Bayram Yeşiltaş

COLOR KNOWLEDGE AND THE FORMATION OF THE DIFFERENT COLORTONES IN OFFSET PRINTING The concept of color formation comes to life by a light striking (hitting) a opposite object. Without the existence of light there would be no color possible to seen by people. Generally the colors are based on two groups. These are materialistic colors and lightbased colors. The mixing process of the materialistic colors such as cyan, magenta and yellow colors together enables the formation of black color. The foundation of the light color turns into a dim light color when red, green and purple colors are united with each other. We are going to focus on materialistic color mixage in these two separate color foundation as for as materialistic color mixage is used in offset printing. The computer technology continues to develope in printing field as it develops in every other fields. As the mentioned technology has spreaded into medium and small sized printing offices, now it is possible separate and edit color procedure in computer. The rules of color changing process in a computer based environment, the separetion of the colors editing process and the color transmissions are obserued.The important factors plays a great deal in offset printing tecnique and these fctors determines it's final quality degree and these factors are paper, cartoon, tin, the age the machine, the dampation system (alcoholic convention) and the quality of the film, model, ink, rubber (blanket) damping water and the assistant materials. A quality print out enables a positive impact and a attractive appearence on peoples eye. In order to maintain this quality the negative factors should be eliminated. The color separation of the original piece and the selection of the printing machine according to it's material and it's impact on the formation of the color will be impacts on the formation of the color will be researced and submitted. The color error lue to printed paper (material) frictions is tested and shown in a chart form. The color resistance to light rays are tested and also subwitted as a chart. May - 2002
Keywords: Ofset Baskı